Human Resource Management in the Digital Era - Herman Herman; Shofia Amin; Zulfina Adriani; Sry Rosita (Dinasti International Journal of Education Management And Social Science, 2025)
The aim of this research is to see the extent of the role of Human Resource Management (HRM) in the Digital Era. The method used in this research is "systematic literature review (SLR)". The results of the study are that human resources can create value and need to be seen as an important part of interdepartmental business analysis. methodology used to view the perceptions of human resource management researchers regarding the function or role of human resource management in the digital world. These are all interrelated and will have a multiplier effect on improving individual and organizational performance. In conclusion, effective and appropriate Human Resources are needed so that individual and organizational performance can improve optimally and sustainably.